Institutional Alignment and Policy Gaps in Adolescent Maternal Healthcare: A Health Administration Perspective on Reproductive Service Delivery - Andi Nurzakiah Amin; Dian Anggraeni Rachman; Samsiana (Science Tech Group, 2026)
Adolescent maternal healthcare remains a critical challenge in many health systems, particularly in ensuring effective service delivery amid complex administrative and policy environments. This study aims to examine the influence of institutional alignment and policy gaps on service delivery performance from a health administration perspective. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with data collected from 215 healthcare professionals, including midwives, nurses, physicians, and healthcare administrators. The measurement model evaluation confirmed satisfactory validity and reliability, with all constructs meeting the required thresholds. The structural model results revealed that institutional alignment has a significant positive effect on service delivery performance (β = 0.45, p < 0.001), while policy gaps have a significant negative effect (β = −0.38, p < 0.001). Additionally, institutional alignment significantly reduces policy gaps (β = −0.52, p < 0.001), indicating a mediating relationship. The model explains 62% of the variance in service delivery performance (R² = 0.62), demonstrating substantial explanatory power. These findings indicate that improving healthcare performance requires not only strong institutional alignment but also the reduction of policy implementation gaps. This study highlights the importance of an integrated governance approach to enhance the effectiveness, accessibility, and quality of adolescent maternal healthcare services.